Relationship Between Nurses’ Adult CPR‐Related Knowledge, Attitudes and Self‐Efficacy: A Cross‐Sectional Study - Ayman Ateq Alamri (Nursing in Critical Care, 2026)
ABSTRACT Background Cardiac arrest in the hospital (IHCA) is a dramatic phenomenon that requires efficient and urgent response in which nurses are often the first responders. Aim The aim of the study was to establish the relationship between nurses' knowledge, attitudes and self‐efficacy with respect to adult cardiopulmonary resuscitation (CPR) in acute care at King Fahad Hospital, Saudi Arabia. Study Design A cross‐sectional, descriptive‐correlational research design was used. Registered nurses were surveyed using a structured questionnaire assessing CPR‐related knowledge, attitudes and self‐efficacy. Results Total 362 nurses have completed the questionnaire. Nurses demonstrated generally adequate CPR‐related knowledge, positive attitudes and good self‐efficacy towards CPR. Significant positive correlations were observed between knowledge and attitudes ( ρ = 0.696, p < 0.0001), knowledge and self‐efficacy ( ρ = 0.772, p < 0.0001) and attitudes and self‐efficacy ( ρ = 0.812, p < 0.0001). Lower knowledge scores were observed in defibrillation‐related procedures and medication administration during CPR. Conclusions The findings indicate differences across cognitive (knowledge), affective (attitudes) and self‐efficacy domains in nurses' preparedness, which may inform targeted educational strategies to strengthen CPR preparedness among nurses. Relevance to Clinical Practice The study supports the need for targeted interventions such as simulation‐based training, repeated CPR education and structured debriefing sessions. Institutional policies should emphasise training frequency, policy communication and role clarity to align with international resuscitation standards and improve IHCA outcomes.